2018
DOI: 10.1590/0074-02760170433
|View full text |Cite
|
Sign up to set email alerts
|

Validation and reliability of the rapid diagnostic test ‘SD Bioeasy Dengue Duo’ for dengue diagnosis in Brazil: a phase III study

Abstract: BACKGROUNDThe diagnosis of dengue is complex. Until recently, only specialised laboratories were able to confirm dengue infection. However, this has changed with the newly available immunochromatographic rapid tests. Early diagnosis is of great interest, and point-of-care rapid tests have been increasingly used in Brazil. Most of those tests have not undergone validation in the Brazilian population. In this context, we decided to evaluate a rapid test introduced in the Federal District (FD).OBJECTIVESTo estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(29 reference statements)
1
8
1
2
Order By: Relevance
“…Previous evaluations of this RDT found much greater sensitivities, ranging between 75.5–97.5% [58,1620]. The diversity in patients’ clinical characteristics, frequency of primary and secondary infections, infecting DENV serotypes, and reference dengue diagnostic methods used between our study and other investigations may explain the observed differences in the measured sensitivities [15,16,21].…”
Section: Discussioncontrasting
confidence: 41%
“…Previous evaluations of this RDT found much greater sensitivities, ranging between 75.5–97.5% [58,1620]. The diversity in patients’ clinical characteristics, frequency of primary and secondary infections, infecting DENV serotypes, and reference dengue diagnostic methods used between our study and other investigations may explain the observed differences in the measured sensitivities [15,16,21].…”
Section: Discussioncontrasting
confidence: 41%
“…al. 48 ) was made by High Pure Viral Nucleic Acid Version 18 Kit (Roche Diagnosis), with a single step reaction provided by LightCycler Multiplex RNA Virus Master Version 03 (Roche Diagnosis). RNA standards, in a final volume of 20 µl, were reverse transcribed; Primer concentration was 0.5 µM and probe was used in a concentration of 200 nM.…”
Section: Viral Load By Rt-pcrmentioning
confidence: 99%
“…Such pre-existing antibodies would compete with the monoclonal antibodies (MAbs) of RDTs [29] and interfere with the reaction monitored by RDTs. RDT signals upon secondary infection usually are weaker than those detected upon primary infection [14, 15, 20, 23, 25, 26, 30, 31]. Therefore, it would be desirable to have more-sensitive and less-cross-reactive antigen-detecting RDTs for accurate DENV diagnosis.…”
Section: Introductionmentioning
confidence: 99%